Neurodegenerative disease risk among former international rugby union players. Issue 12 (4th October 2022) - Russell, Emma R; Mackay, Daniel F; Lyall, Donald; Stewart, Katy; MacLean, John A; Robson, James; Pell, Jill P; Stewart, William
Abstract : Background: Autopsy studies of former contact sports athletes, including soccer and rugby players, frequently report chronic traumatic encephalopathy, a neurodegenerative pathology associated with traumatic brain injury. Nevertheless, little is known about the risk of neurodegenerative disease in these populations. We hypothesised that neurodegenerative disease risk would be higher among former elite rugby union players than the general population. Methods: We conducted a retrospective cohort study accessing national electronic records on death certification, hospital admissions and dispensed prescriptions for a cohort of 412 male Scottish former international rugby union players and 1236 members of the general population, matched to former players by age, sex and area socioeconomic status. Mortality and incident neurodegenerative disease diagnoses among former rugby players were then compared with the matched comparison group. Results: Over a median 32 years follow-up from study entry at age 30 years, 121 (29.4%) former rugby players and 381 (30.8%) of the matched comparison group died. All-cause mortality was lower among former rugby players until 70 years of age with no difference thereafter. During follow-up, 47 (11.4%) former rugby players and 67 (5.4%) of the comparison group were diagnosed with incident neurodegenerative disease (HR 2.67, 95% CI 1.67 to 4.27, p<0.001). Conclusions: This study adds to our understanding of the association between contact sports participation and the risk of neurodegenerative disease. While further research exploring this interaction is required, in the meantime strategies to reduce exposure to head impacts and head injuries in sport should be promoted.